Rancang Bangun Website Kebun Raya di Dinas Kominfo Kabupaten Gianyar - Putra, Putu Gede Weda Pramana; Sugiartawan, Putu; Putra, I Wayan Kintara Anggara (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2021)
The development of technology is so rapid that we as humans must keep pace with the rapid development of technology and switch from conventional methods to more modern ways. The development of technology today is very helpful for human life, one of which is the internet. Almost everyone is currently connected to the internet because of the ease with which information can be obtained via the internet. The internet today as one of the existing information facilities is very influential for the dissemination of information through technology called a website. Especially in the field of tourism, web-based information systems are very important as a media for promotion and information to support the advancement of tourism. Like the Gianyar Botanical Gardens, which is located in the Banjar Pilan Banjar, Kerta, Payangan, Gianyar Regency. This area is still not widely known due to the limited information available. limited information due to still using media posters, billboards, and brochures for media promotions, so the lack of coverage that can be reached from these media in addition to the amount of energy and costs required. So from this research it can be concluded how to disseminate information to a wider audience by using a website-based information system in this design using a waterfall-based system development media.